Book Review: Filsafat Pendidikan Kristen: Meletakkan Fondasi dan Filosofi Pendidikan Kristen di Tengah Tantangan Filsafat Dunia - Gea, Leniwan Darmawati (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2024)
The book "Philosophy of Christian Education: Laying the Foundations and Philosophy of Christian Education amidst the Challenges of World Philosophy" written by Khoe Yao Tung makes an important contribution to Christian Education, because the book aims to stimulate educators to think about issues of metaphysics, epistemology and axiology to develop a philosophy based on truth from a Christian perspective. This book is needed to equip educators to understand the importance of philosophy for Christian education, which has become increasingly unrecognized recently. To fulfill this, the author outlines several schools of thought in philosophy on an ongoing basis to bring the reader to a clear understanding of the historical path of its development. Of the philosophers referred to, most of them are not Christian thinkers. Nevertheless, the authors show that their thoughts are important for the purposes of critical analysis of Christian thinkers. The goal is that by understanding their thinking, Christians can understand unbiblical thought discourse and avoid it responsibly and of course with solid and quality arguments.